(untitled) (Fiep Bulletin - online, 2011)
The objective of the study was to determine the possible influences of the previous warming in physiological-variable and Hemodinâmicos proceeding from the test of race of go- and -comes of 20 m. 17 teenagers had participated of this study. The protocol of Luc Léger & Lambert (1982), that it carries through the estimate of the VO2max, and taking in consideration the attainment of this during the last period of training, we can make inferences the intensity of VO2max and find (IVO2max). First the evaluated ones had carried through the protocol without heating ( LLSA), and with an interval of at least 48 hours, they had carried through a reverse speed-test with heating (LLCA) previous that consisted of 7 minutes of race to 8Km.h -1 speed of. In both the situations before the test for heart rate at rest was measured, as well as arterial pressure was measured. After the test to HR and the AP were measured so that the exhaustion was characterized. By means of the product between AP systolic and HR may-obtain the double-product before and after. In 5 minutes after the test HR was measured every minute.The possible differences have been highlighted using-if the t student test for samples repeated, with the level of significance pre-set at p